Efficacy and safety of modified Xuanbai Chengqi Decoction as an adjunctive treatment for severe pneumonia: a systematic review and meta-analysis - Tie, Yifu; Liu, Han; Zhang, Tong; Meng, Tianwei; Liang, Qun (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the efficacy and safety of Modified Xuanbai Chengqi Decoction as an adjunctive therapy for severe pneumonia (SP) and to explore its clinical rationale.MethodsA comprehensive search was performed in CNKI, Wanfang, VIP, CBM, Cochrane Library, PubMed, and Embase, covering database inception to November 2024. Randomized controlled trials that investigated the combination of Modified Xuanbai Chengqi Decoction with standard therapy for severe pneumonia were included. Quality evaluation, meta-analysis, and bias assessments were performed with Review Manager 5.4, using risk ratios and mean differences (MD), both with 95% confidence intervals to estimate effects.ResultsA total of 14 RCTs involving 1,061 participants met the inclusion criteria. Meta-analysis indicated that adjunctive treatment with the decoction achieved better overall response rates [RR = 1.21, 95% CI (1.14, 1.28), P < 0.00001] and demonstrated significant reductions in interleukin-6 (IL-6, MD = −15.07, 95% CI (−17.31, −12.83), P < 0.00001), interleukin-13 (IL-13, MD = −7.30, 95% CI (−7.82, −6.79), P < 0.00001), and tumour necrosis factor-α (TNF-α, MD = −0.56, 95% CI (−0.64, −0.48), P < 0.00001), high-sensitivity C-reactive protein (hs-CRP, MD = −2.09, 95% CI (−2.47, −1.71), P < 0.00001), procalcitonin (PCT, MD = −2.04, 95% CI (−2.55, −1.53), P < 0.00001), arterial blood gas lactate (LaC, MD = −2.28, 95% CI (−2.45, −2.11), P < 0.00001), mechanical ventilation time (MD = −120.03, 95% CI (−130.14, −109.92), P < 0.00001), clinical pulmonary infection score (CPIS, MD = −2.71, 95% CI (−3.95, −1.82), P < 0.00001), Acute Physiology and Chronic Health Evaluation II (APACHE II) score (MD = −7.41, 95% CI (−7.54, −7.28), P < 0.00001), and ICU transfer rate [RR = 22.88, 95% CI (6.68, 78.32), P < 0.00001].ConclusionModified Xuanbai Chengqi Decoction appears advantageous as an adjunct for SP treatment, but the evidence remains insufficient to support widespread application owing to the low quality of the included research. Future studies should incorporate higher-quality RCTs and assess drug safety and cost-effectiveness in a rigorous manner.